CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN PANDEMI COVID-19: STUDI LITERATUR DAN LAPORAN KEBERLANJUTAN - Putri, Putu Ambika Apsari Kesuma; Urahman, Auliya; Prastiwi, Arum (Buletin Studi Ekonomi, 2024)
This research aims to understand Corporate Social Responsibility (CSR) by companies before and during the pandemic. The research method uses a qualitative approach by analyzing literature studies. A total of 21 articles were explored, covering CSR during the Covid-19 pandemic in various countries from various continents. In addition, this research analyzes the sustainability reports of companies in Indonesia to compare CSR practices before and during the pandemic, with random selection of companies of various types. The results of the research state that the implementation of (CSR) by companies during the Covid-19 pandemic has increased. This research seeks to provide a comprehensive picture of CSR implementation by companies during the Covid-19 pandemic crisis, by comparing CSR activities before and during the pandemic. Recommendations for increasing the number of review articles were given based on the finding that the number of articles that had been reviewed was still relatively small.